(untitled) (Indian Journal of Chemistry (IJC), 2023)
Diabetes mellitus is a complex endocrine disorder of global concern, associated with the development of metabolism-related complications in the body, and is spreading like an epidemic. With a variety of medical treatments available and no absolute cure for this disorder, there is a great need to search for safe and efficacious antidiabetic molecules, which can be achieved using high throughput screening protocols or in silico screening techniques. However, many synthetic molecules are available for the purpose, use of natural products is known to be viable owing to lesser side effects. Thus, in the present study, the phytochemical investigation of Plumeria alba, known for antidiabetic properties, was carried out to isolate 12 compounds in pure form, using various chromatography and crystallization techniques. Further, the in silico screening for antidiabetic efficacy was done for 22 compounds including the literature known and the above isolated ones. AutoDock 4.2 and GROMACS software were utilized for analyzing inhibition of α-glucosidase (PDB ID: 2ZE0) through molecular docking and MD simulations. Steroids and triterpenes viz. lup-20(29)-ene-3-yl-hexanoate (PA-1), 4a-methyl-5a-stigmast-7,24(28)-dien-3b-ol (PA-5), 4a-methyl-5a-stigmast-7,24(28)-dien-3b-O-glucoside (PA-7), lup-20(29)-en-3-one (PA-8), 3b-hydroxy-12-ursene-28-oic acid (PA-12), β-sitosterol (L1) and β-amyrin (L3) displayed high binding energies from -9.80 to -9.03 kcal/mol. The physicochemical and ADME analysis were also done on the best leads, using Molinspiration cheminformatics and PreADMET servers respectively, to further strengthen their suitability as α-glucosidase inhibitors.